Effective Governmental Public Relations Reconciled with governmental policies and the citizens’ rights to information: a Malaysian legal perspective - Mohamad Rizal Abdul Rahman, (Fakulti Undang - Undang, 2001)

(untitled)
A two-way communication skill just leads to either one of two possible results: mutual understanding or diverse misunderstanding. Imagine a country without mutual understanding and two-way communication between the government and the subjects; the possibility that such a country will later collapse is very close. In return to the information provided by the government to the public, and vice versa, then only the former would be able to remedy any complaints or constraint suffered by the latter. Thus, effective public relations ensures citizen’s involvement and government responsiveness to societal needs. This in turn brings us to the notion of the right to information. It is nowhere stated in express words throughout the Fundamental Liberties heading in our Federal Constitution, yet implication, though, may suggest such right being part of the so-called basic rights. But once policies demand its dominance, must such right give its way? Any government kneeling in prayer for mutual trust from its very citizens, is to reconcile these three things-effectiveness in public relations to ensure the satisfaction of the notion of right to information but with an exceptional stand to its policies